A study on factors influencing government servants when choosing financial institutions / Mohd Saiful Azrie Tamjudin - Tamjudin, Mohd Saiful Azrie (2013)
Recently in July 2013, Bank Negara Malaysia (BNM) has implement a set of measures effective immediately in order to curb rising trend of household indebtedness and reinforcing responsible lending practices by key credit providers. The governor of Bank Negara Malaysia, Tan Sri Dr. Zeti Akhtar Aziz stated the measures were reducing the maximum tenure of personal loans to 10 years and properties financing to 35 years. Thus, lead to the spike of loan application in Malaysia where household are rushing for applying loan with longer loan tenure. This study is conduct to focus on financial loan made by government servant in Kota Kinabalu. The aim is to determine how government servant chooses their financial institution. However, the study will only focus on government servants with lower class income range. This study is also a part of requirement needed to complete Bachelor of Business Administration with Honors (Marketing).